Association Between Sex-Specific Serum Uric Acid and Non-Alcoholic Fatty Liver Disease in Chinese Adults: A Large Population-Based Study. Issue 17 (May 2015) - Wu, Sheng-Jie; Zhu, Gui-Qi; Ye, Bo-Zhi; Kong, Fan-Qi; Zheng, Zai-Xing; Zou, Hai; Shi, Ke-Qing; Lin, Lu; Braddock, Martin; Huang, Wei-Jian; Chen, Yong-Ping; Zheng, Ming-Hua
Abstract : Abstract: The aim of this study was to examine the association between sex-specific serum uric acid (sUA) levels and NAFLD in a large population-based study. A total of 60, 455 subjects from 2 separate medical centers were included. Sex-specific sUA quartiles (Q1–Q4) were defined: ⩽330, 331–380, 381–435, and ≥436 μmol/L for male; ⩽230, 231–270, 271–310, and ≥311 μmol/L for female. The odds ratios (ORs), hazard ratios (HRs), and 95% confidence intervals (CIs) for NAFLD were calculated across each quartile of sUA, using the Q1 as reference. After adjusting for known confounding variables in this study, the ORs for NAFLD in the cross-sectional population were 1.211 (95% CI 1.109–1.322), 1.519 (95% CI 1.395–1.654), 1.903 (95% CI 1.748–2.072) for Q2, Q3, and Q4, respectively. In the longitudinal population, compared with the reference group, those in Q2, Q3, and Q4 had HRs of 1.127 (95% CI 0.956–1.330), 1.380 (95% CI 1.157–1.644), 1.589 (95% CI 1.310–1.927) for NAFLD, respectively. Analysis for the sex-specific subgroup showed the adjusted ORs for Q4 versus Q1 were 2.898 (95% CI 2.36–3.588) in female and 1.887 (95% CI 1.718–2.072) in male in the cross-sectional population. In the longitudinal population, the HRs for the Q4 were 2.355 (95% CI 1.702–3.259) in female and 1.249 (95% CI 0.975–1.601) in male, compared with Q1. We report that a sex-specific sUA level is independently associated with NAFLD. The association between sUA and NAFLD was significantly greater in females than in males.